Analisis Kelayakan Kampung Namicalung Menjadi Desa Wisata Sarung Tenun Legendaris Majalaya - Shinta Larista; Rheinanda Awliya Agista; I Dewa Alit Dwija Putra (Ridwan Institute, 2023)
Woven textiles, a vital aspect of Indonesia's cultural heritage, greatly influence the Nusantara archipelago's identity. Majalaya in West Java, known as the